KORELASI KEKUATAN OTOT LENGAN KEKUATAN OTOT TUNGKAI DAN DAYA LEDAK TUNGKAI TERHADAP KEMAMPUAN RENANG GAYA PUNGGUNG 50 METER PADA MAHASISWA PENJASKESREK STKIP PARIS BARANTAI KOTABARU - M Imran Hasanuddin (STKIP Paris Barantai, 2020)
research aims to find out whether: 1) correlation between arm strength and 50 meter backstroke swimming, 2) correlation between leg strength and 50 meter backstroke swimming, 3) correlation between arm's explosive power to 50 meter backstroke swimming, 4) correlation between arm strength, leg strength, and leg explosive power on the 50 meter backstroke swimming among STKIP Paris students. The population of this study is students of PJKR STKIP Paris Barantai. Sample 33 people. The sampling technique is simple random sampling. The data analysis technique used is descriptive and inferential analysis through the SPSS 23 program. The results of the research on STKIP Paris Barantai students showed that; 1) there correlation between arm strength and 50 meter backstroke swimming, amounting to 14.4%; 2) there correlation between leg strength and 50 meter backstroke swimming, 50 meter backstroke swimming, amounting to 13.7%; 3) there correlation between the explosive power of the limbs to the 50 meter backstroke swimming, amounting to 20.5%, and 4) there correlation between the arm strength, leg strength and the explosive power of the limbs to the 50 meter backstroke swimming, amounting to 32.4%, with Fcount 4,627. Keywords: arm strength, leg strength, leg explosive power and backstroke swimming ability.